THE SIGNIFICANCE OF THE IMAGES OF FLOWERS AND NIGHTINGALES IN THE EPIC POEM “KHAMSA” - Xolboyeva , Muslima (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This article examines the artistic expressive potential of the images of flowers and nightingales in Alisher Navoi's epic poem “Khamsa”. The themes covered by the images of flowers and nightingales in the epic poem are analyzed. In particular, the poet's socio-philosophical, moral-enlightenment thoughts are revealed through these images. This article examines the symbolic functions and semantic diversity of the images of the flower and the nightingale in Alisher Navoi’s “Khamsa”. Recognized as the pinnacle of Navoi’s artistic heritage, the “Khamsa” reflects the poet’s philosophical worldview, moral teachings, and spiritual perceptions through a rich system of traditional, mythological, prophetic, and historical images. Among the traditional symbols, the flower and the nightingale occupy a central place due to their polysemantic nature and their ability to convey subtle emotional, philosophical, and didactic meanings. The study analyzes the use of these images in each of the five epics of the “Khamsa”. In “Hayrat ul-abror”, the flower and the nightingale primarily express Sufi-philosophical ideas and moral reflections. In “Farhod and Shirin”, they illuminate the emotional states of the characters and help reveal the depth of Farhod’s love. In “Layli and Majnun”, the imagery is closely linked to natural and seasonal motifs, emphasizing the emotional landscapes of the lovers. “Sab’ai Sayyor” employs these images more frequently, especially in the characterization of Dilorom. In “Saddi Iskandariy”, the flower and nightingale acquire new meanings, symbolizing enlightenment, love, and human virtues. Methodologically, the research draws on comparative-historical, descriptive, classificatory, statistical, and systemic approaches to explore the role of floral and nightingale imagery throughout the “Khamsa”. The findings demonstrate that these symbols serve not only aesthetic and emotional purposes but also contribute to the expression of social, ethical, and philosophical themes. The article concludes that Navoi’s skillful use of these images enhances the artistic value of the “Khamsa” and deepens its ideological content, making them essential components of his poetic world.